Proyecto de factibilidad para la elaboración y comercialización de tortas a base de maíz tierno, en la ciudad de Loja - Calva Jaramillo, Mariana Bacilia (2019)
The main objective of this research work is to determine the feasibility for the elaboration and commercializes of cakes based on sweet corn, in the city of Loja, which serves as a proposal to generate a different business project that gives society a new product and innovative that helps improve eating habits, without neglecting the pleasure of a varied and pleasant diet to the palate of the population. Thus, the specific objectives to be carried out were considered: the market study, the technical study, the legal administrative study, the financial study and finally the evaluation of the project. The methodology used for the research was descriptive where a sample of 381 surveys was determined, which were applied to the families of the city of Loja. To determine the feasibility of the project the market study is undertaken where the required demands are known, so that for the first year the potential demand represents 81% that if they consume cakes that is 44,790 families, the real demand is made up of the 100% equivalent to 309 respondents who stated that they have not consumed cakes of sweet corn (corn), for the effective demand corresponds 100% that is equivalent to 36,280 families who would be willing to acquire the new product offered; The supply for the first year is zero and the unsatisfied demand is 943,272, with these results marketing strategies were proposed focused mainly on marketing (product, price, place and promotion). The technical study was prepared to establish the necessary processes, such as product engineering, plant size, in which the installed capacity that is 100% was determined allows a production of 105,120 cakes based on sweet corn and the one used is 23.74% same that allows a production of 24,960 units for the first year. The company will be located in the city of Loja in the Citadel of Chauffeur San Cayetano, in the streets: Montreal and Los Angeles, place that has access roads and basic services essential for its operation. Also, the legal administrative study was carried out where the business organizational structure was defined, with its respective organization chart, thus determining the manual of functions indicating the tasks and responsibilities for each position, the nature of work and the requirements that the employees that must meet to fill those positions. The financial study described the fixed, deferred assets and working capital, giving a total investment of the project of $ 48,720.80 which will be financed by the capital of the partners by 70% and by a financial institution 30%. Likewise, the results obtained in the financial evaluation determined the feasibility of the project with a NPV of $ 205,998.65; the IRR (Internal Rate of Return) corresponds to 62.77%; Rb / c. (Cost Benefit Ratio) for each dollar invested the company earns 73 cents; the PRC. (Capital Recovery Period), is 1 year, 8 months and 20 days; A.S (Sensitivity Analysis) indicates that the project supports an increase in costs of 39% and a decrease in revenues of 27.34%, therefore, the project is considered feasible, whose conclusions and recommendations so determine.